Identification and quantification of plasticizers, bisphenol, and environmental toxic mineral elements residues in medicines from Tunisian markets - Beltifa, Asma; Alibi, Sana; Turco, Vincenzo Lo; Mansour, Hedi Ben; Di Bella, Giuseppa (Environmental science and pollution research international, 2021)
In this study, 18 plasticizer (phthalates, adipates, sebacates, and others) residues in sixteen medicines available in Tunisian pharmaceutical markets are evaluated by MSPD combined with GC-MS. In parallel, in this research, UPLC-MS/MS technique was performed to detect bisphenol A, and cadmium, lead, chromium, cobalt, nickel, mercury, selenium, and arsenic levels were determined by ICP-MS. The maximum daily ingested mass of mineral elements was calculated and compared with permissible daily exposure limits published by USP NF 2013. Our results demonstrated that the 50% of drugs contained similar concentrations of di-ethyl adipate. Di-isobutyl phthalate was found in a single sample with a high concentration (1.07mgkg -1 ). Di-methyladipate was also present in only one sample. Diethyl phthalate was detected in three medicines: the highest concentration (17.03mgkg -1 ) was found in capsules. The other plasticizers and bisphenol A levels were below the limits of quantification in the all samples. All tested products were safe for use, except two clay-originated products. Concentrations and the maximum daily ingested mass of lead and arsenic were higher than recommended limits. The use of these medicines should require more attention taking into account the serious hazards of heavy metals to human health.